2016
DOI: 10.1002/er.3673
|View full text |Cite
|
Sign up to set email alerts
|

Reaction conditions of ultrasound-assisted production of biodiesel: A review

Abstract: Summary Ultrasound‐assisted biodiesel production is an emerging technology that features high energy density, high conversion efficiency, and environment friendliness. This review evaluates the influence of process parameters, including ultrasonic power, ultrasonic frequency, catalyst dosage, alcohol/oil ratio, reaction temperature, reaction time, and alcohol type, on the yield of ultrasonic‐assisted production of biodiesel. Limitations associated with ultrasonic‐assisted production of biodiesel are also analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 130 publications
(267 reference statements)
0
9
0
Order By: Relevance
“…An interesting alternative is to use ultrasonication for mixing, heating, and mass transfer between different phases of reaction bulk. This process permits adequate mixture reagents and increases the reaction temperature by the cavitation process, bubble bursting formed in ultrasound frequencies into water based on negative, and positive pressions with expansion and compression, reducing costs, energy consumption, and the alcohol:oil ratio.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting alternative is to use ultrasonication for mixing, heating, and mass transfer between different phases of reaction bulk. This process permits adequate mixture reagents and increases the reaction temperature by the cavitation process, bubble bursting formed in ultrasound frequencies into water based on negative, and positive pressions with expansion and compression, reducing costs, energy consumption, and the alcohol:oil ratio.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that 88% of the energy used by humans is derived from non-renewable fossil fuels, which result in an urgent demand for sustainable and green energy [1]. It is reported that 88% of the energy used by humans is derived from non-renewable fossil fuels, which result in an urgent demand for sustainable and green energy [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that 88% of the energy used by humans is derived from non-renewable fossil fuels, which result in an urgent demand for sustainable and green energy [1]. A number of energy production and consumption giants, such as British Petroleum, Chevron, General Atomics, Boeing, Virgin Airlines, Japan Airlines, and New Zealand Airlines, invested in the research and development of microalgae energy [1]. Lignocellulosic material is the most promising feedstock for bioethanol production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations